Teaching Students Morals to Teachers in the Digital Age: Analysis of the Impact of Gadgets and Social Media - Mihmidaty Ya'cub; Moch. Sya’roni Hasan; Mar'atul Azizah; Nisrina Dianing Putri; Ati Dingpanoh (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2026)
The development of digital technology, particularly the use of gadgets and social media, has brought significant changes to the world of education, including in shaping students' attitudes towards teachers. This study aims to analyze the impact of gadgets and social media use on students' attitudes towards teachers at MA Syafi'iyah Terpadu Ngoro Jombang. This study uses a qualitative approach with a descriptive research type. Data were obtained through in-depth interviews, observations, and documentation involving the principal, teachers, and students. Data analysis was conducted using an interactive model that included data collection, data reduction, data presentation, and conclusion drawing, while data validity was maintained through triangulation of sources and methods. The results showed that the use of gadgets and social media had a dual impact on students' morale towards teachers. The negative impacts found included a decline in learning concentration, discipline, and students' communication ethics towards teachers. However, the use of gadgets and social media also had a positive impact when used wisely as a learning support tool. Madrasahs' efforts to overcome the negative impacts are carried out through the enforcement of rules and regulations, character building, and continuous guidance for students. This study emphasizes the importance of integrating character education with digital literacy in Islamic education so that the use of technology remains in line with Islamic values